2023
DOI: 10.3390/cells12020311
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Crosstalk between Exosome-Mediated Ferroptosis and Diseases for Pathogenesis and Treatment

Abstract: Ferroptosis is a type of iron-dependent cell death caused by ferrous iron overload, reactive oxygen species generation through the Fenton reaction, and lipid peroxidation, leading to antioxidative system dysfunction and, ultimately, cell membrane damage. The functional role of ferroptosis in human physiology and pathology is considered a cause or consequence of diseases. Circulating exosomes mediate intercellular communication and organ crosstalk. They not only transport functional proteins and nucleic acids d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…In the I/R myocardial injury model, it was shown that exosomes derived from hUCB-MSCs and loaded with exosomal miR-23a-3p inhibited ferroptosis by regulating iron metabolism independent of the GPX4 pathway [233]. The role of exosomes in ferroptosis-related pathogenic mechanisms in various diseases is described in detail in this review [234]. Figure 5 shows the scheme of hepatocyte protection from ferroptosis due to MSC and MSC derivatives.…”
Section: Anti-ferroptosis and Anti-pyroptosis Effects Of Mscmentioning
confidence: 99%
“…In the I/R myocardial injury model, it was shown that exosomes derived from hUCB-MSCs and loaded with exosomal miR-23a-3p inhibited ferroptosis by regulating iron metabolism independent of the GPX4 pathway [233]. The role of exosomes in ferroptosis-related pathogenic mechanisms in various diseases is described in detail in this review [234]. Figure 5 shows the scheme of hepatocyte protection from ferroptosis due to MSC and MSC derivatives.…”
Section: Anti-ferroptosis and Anti-pyroptosis Effects Of Mscmentioning
confidence: 99%
“…91 Circulating exosomes can mediate cell-to-cell communication and organ cross talk, serving as carriers of functional proteins and nucleic acids from parental cells. 92 Cancer-associated fibroblasts (CAFs) secrete various bioactive substances, including exosomes. For example, CAFs Obesity is strongly linked to the poor prognosis in advanced colorectal cancer patients, with unclear mechanisms.…”
Section: Ferroptosismentioning
confidence: 99%
“…Exosomes have also shown their potential in ferroptosis‐based cancer treatment, validated in multiple types of tumors 91 . Circulating exosomes can mediate cell‐to‐cell communication and organ cross talk, serving as carriers of functional proteins and nucleic acids from parental cells 92 . Cancer‐associated fibroblasts (CAFs) secrete various bioactive substances, including exosomes.…”
Section: Exosomes In Different Types Of Pcdmentioning
confidence: 99%
“…Notably, exosome and ferroptosis may interplay with each other [ 10 , 11 , 12 , 13 , 14 , 15 ]. Exosomes may enhance or suppress ferroptosis in several diseases and cancers [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of ferroptosis may be triggered via exosome-mediated regulation that acts on ferroptosis signaling [ 10 ]. Exosomes may deliver biomolecules to recipient cells and, in turn, regulate ferroptosis-modulating signaling and response [ 11 , 12 ]. For example, breast cancerous exosomes suppress migration mediated by ferroptosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%